2007
DOI: 10.1007/s00251-007-0206-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of porcine classical and nonclassical MHC class I expression

Abstract: Major histocompatibility complex (MHC) class I molecules comprise a family of polymorphic cell surface receptors consisting of classical 1 a molecules that present antigenic peptides and nonclassical 1 b molecules. Gene expression for human classical and nonclassical MHC class I molecules has been shown to be differentially regulated by interferon, with variation in the nucleotide sequence of promoter regions, resulting in differences in interferon inducibility and basal levels of gene transcription. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Pig conceptus trophectoderm cells express high amounts of IFN-␥ mRNA from day 13 through day 20 of pregnancy, and immunoreactive IFN-␥ localizes to perinuclear membranes typically occupied by endoplasmic reticulum and Golgi apparatus as well as cytoplasmic vesicles within trophectoderm cells, suggesting trafficking and secretion of IFN-␥ into the uterine lumen (28,31). Interestingly, SLA-1, SLA-2, and SLA-3, but not SLA-6 or SLA-7, were reported to respond to both IFN-␥ and IFN-␣ in a pig kidney cell line (55). Although results of the present study are consistent with those of Tennant et al (55) for SLA-1, SLA-2, and SLA-3, there are differences between in vivo and in vitro results for SLA-6 and SLA-7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pig conceptus trophectoderm cells express high amounts of IFN-␥ mRNA from day 13 through day 20 of pregnancy, and immunoreactive IFN-␥ localizes to perinuclear membranes typically occupied by endoplasmic reticulum and Golgi apparatus as well as cytoplasmic vesicles within trophectoderm cells, suggesting trafficking and secretion of IFN-␥ into the uterine lumen (28,31). Interestingly, SLA-1, SLA-2, and SLA-3, but not SLA-6 or SLA-7, were reported to respond to both IFN-␥ and IFN-␣ in a pig kidney cell line (55). Although results of the present study are consistent with those of Tennant et al (55) for SLA-1, SLA-2, and SLA-3, there are differences between in vivo and in vitro results for SLA-6 and SLA-7.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SLA-1, SLA-2, and SLA-3, but not SLA-6 or SLA-7, were reported to respond to both IFN-␥ and IFN-␣ in a pig kidney cell line (55). Although results of the present study are consistent with those of Tennant et al (55) for SLA-1, SLA-2, and SLA-3, there are differences between in vivo and in vitro results for SLA-6 and SLA-7. It is perhaps not surprising that stromal cells in vivo, which have distinct spatial relationships to other cell types and the extracellular matrix, respond differently to IFNs than do isolated and cultured kidney cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only the SLA-1, SLA-2 , and SLA-3 genes encode functional proteins with known relevance to CD8 T cell activation. Of the 3 SLA loci, the SLA-2 allele is transcribed at a higher level than SLA-1 , and SLA-3 is the allele with the lowest transcription level (68). Although thousands of SLA class I alleles are expected to exist, only 193 classical class I alleles have been identified and officially designated by the International Society for Animal Genetics (ISAG) and the International Union of Immunological Societies (IUIS) Veterinary Immunology Committee (VIC) SLA (ISAG/IUIS-VIC) Nomenclature Committee thus far, including 70 SLA-1, 87 SLA-2, and 36 SLA-3 alleles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SLA-Ib genes are expressed in a less restricted manner than the HLA-Ib genes [12,13] despite a predominant transcription in the lymphoid organs, the lung and the digestive tract [13]. In addition, conversely to the SLA-Ia genes, transfection experiments have revealed that the promoters of SLA-7 and SLA-6 do not respond to interferon, suggesting distinct regulatory systems for pig MHC class Ia and Ib genes, as in human [14]. Our aim was to focus on the transcription of the SLA-7 gene known to have a unique reference transcript [12].…”
Section: Introductionmentioning
confidence: 99%